Development of LKPD Based on the Scientific Approach-Based Hadith Recount Textbook for Grade VII Junior High School Students - Ramadhani, Bella Novia; Imron, Kristina; Muhammad, Kemas; Ramadhan, Muhammad Kevin; Al-Hajj, Ahmad Fadhil; Angraini, Resti Adelicka (Yayasan Indonesia Emerging Literacy Education, 2025)
This study aims to develop and determine the effectiveness of Student Worksheets (LKPD) for muhawarah hadithah of grade VII junior high school students. The approach used is The scientific approach consists of five key steps: observing, questioning, experimenting, reasoning, and communicating findings. In the context of research, the method used is Research and Development (R&D), structured within the 4D model, which includes the stages of: Define, Design, Develop, and Disseminate. The results of the study indicate that the LKPD developed has good validity based on the assessment of material experts (84%) and media experts (87%) with a very valid category. Meanwhile, in terms of the effectiveness of the LKPD muhawarah hadithah of grade VII junior high school students, it is 71%. From the results of the effectiveness test, it can be concluded that the development of the LKPD is based on the muhawarah hadithah textbook is very effective to use. SThe significance between learning outcomes using teaching materials developed in the pre-test and post-test normality test with a sig. value of 0.000, homogeneity testAsymp.Sig. (2-Tailed) in the pre-test was 0.935, paired sample test Sig. (2-Tailed) of 0.001, and the n-gain score test withthe average obtained was 0.4901.